MARKETING COMMUNICATION STRATEGY IN HEALTH BUSINESS OF NUTRITION CLUBS - Astria, Kadek Kiki; Damastuti, Riski; Aprilia, Monika Pretty; Erlistyarini, Yulinda (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
Health products circulating in society are subject to many regulations, one of which is the marketing communication activities. Herbalife is one of the health products that has been available in Indonesia for quite some time and has many customers. This product has a marketing communication strategy that differs from other health products. Nutrition Club is a nutrition house that sells products from Herbalife, using eight elements in the marketing communication mix. These elements include advertising, sales promotion, event and experience, PR and publicity, direct marketing, interactive marketing, sales promotion, and personal selling. This research employs in-depth interviews with 10 Nutritional Clubs spread across Jakarta, Denpasar, and Yogyakarta. Research shows that all interviewed Nutrition Clubs use the eight elements of the marketing communication mix, but their focus varies based on consumer backgrounds and human resource capabilities. Limitations in these resources hinder effective segmentation and targeting, especially for millennials. However, educational communication and lifestyle strategies help boost consumer interest in some nutrition clubs.